Impaired Clearance of Apoptotic Cells in Chronic Inflammatory Diseases: Therapeutic Implications - Szondy, Zsuzsa; Garabuczi, Éva; Joós, Gergely; Tsay, Gregory J.; Sarang, Zsolt (Frontiers in Immunology, 2014)
In healthy individuals billions of cells die by apoptosis every day. Removal of the dead cells by phagocytosis (a process called efferocytosis) must be efficient to prevent secondary necrosis and the consequent release of proinflammatory cell contents that damages the tissue environment and provokes autoimmunity. In addition, detection and removal of apoptotic cells generally induces an anti-inflammatory response. As a consequence improper clearance of apoptotic cells, being the result of either genetic anomalies and /or a persistent disease state, contributes to the establishment and progression of a number of human chronic inflammatory diseases such as autoimmune and neurological disorders, inflammatory lung diseases, obesity, type 2 diabetes or atherosclerosis. During the past decade our knowledge about the mechanism of efferocytosis has significantly increased, providing therapeutic targets through which impaired phagocytosis of apoptotic cells and the consequent inflammation could be influenced in these diseases.